Oxygen Absorption in Electrocatalyst Layers Detected by Scanning Electrochemical Microscopy - Moghaddam Mahdi; Peljo Pekka (Wiley, 2025)
Scanning electrochemical microscopy (SECM) is able to track the local electrochemical activity of an electrolyte-immersed substrate employing an ultra-micro-electrode (UME) in micrometer-scale spatial resolution. In this study, SECM is employed to investigate the presence of oxygen in the electrocatalyst layers of polymer electrolyte membrane fuel cells and electrolyzers. Approach curves on electrocatalyst layers with the tip potential set for oxygen reduction reveal that a significant amount of oxygen is absorbed in the catalyst layer. We confirm that the coexistence of Nafion ionomer and carbon black leads to oxygen confinement. It is suggested that this oxygen is confined within the hydrophobic parts of the self-assembled Nafion on the graphitic surfaces of the carbon black.